Implementing smart city solutions: smart city map and city drop - Rotună, Carmen Ionela; Cîrnu, Carmen Elena; Gheorghiță, Alexandru (Calitatea Vieții, 2017)
Representing the new trend in city development, smart city represents an emerging topic. The paper provides an overview of the smart city concept, focusing on the developing of the subject in Romania and presenting two smart city applications developed both part as smart city solutions, and as the Smart City Map (that provides geospatial information services and accessible data for the general public to search and find out information on specific subjects such as geographic locations, buildings, natural environment and public facilities) and City Drop application (which facilitates access and guides users to local cultural places and events). Smart City solutions benefits are efficient resource utilization, increased quality of life, higher levels of transparency and openness towards citizens.